The Impact of Color Space and Intensity Normalization to Face Detection Performance - I Nyoman Gede Arya Astawa; I Ketut Gede Darma Putra; I Made Sudarma; Rukmi Sari Hartati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this study, human face detection have been widely conducted and it is still interesting to be research. In this research, strong impact of color space for face i.e., many and multi faces detection by using YIQ, YCbCr, HSV, HSL, CIELAB, and CIELUV are proposed. In this experiment, intensity normality method in one of the color space channel and tested the faces using Android based have been developed. The faces multi image datasets came from social media, mobile phone and digital camera. In this experiment, the color space YCbCr percentage value with the image initial value detection before processing are 67.15%, 75.00%, and 64.58% have been reached. Then, after the normalization process are 83.21%, 87.12%, and 80.21% have been increased. Furthermore, this study showed that color space of YCbCr have reached improvement percentage